2003
DOI: 10.1016/s0002-9440(10)63447-5
|View full text |Cite
|
Sign up to set email alerts
|

Decorin Inhibition of PDGF-Stimulated Vascular Smooth Muscle Cell Function

Abstract: Decorin is a small proteoglycan that binds to transforming growth factor-beta (TGF-beta) and inhibits its activity. However, its interaction with platelet-derived growth factor (PDGF), involved in arterial repair after injury, is not well characterized. The objectives of this study were to assess decorin-PDGF and decorin-PDGF receptor (PDGFR) interactions, the in vitro effects of decorin on PDGF-stimulated smooth muscle cell (SMC) functions and the in vivo effects of decorin overexpression on arterial repair i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(40 citation statements)
references
References 38 publications
3
36
0
Order By: Relevance
“…However, LRP-1 also regulates signaling cascades by binding growth factors such as platelet-derived growth factor (49), CTGF (50), and TGF-␤ (51, 52). Interestingly, several of these molecules also bind decorin (53)(54)(55). Type V TGF-␤ receptor was found to be identical to LRP-1 (56) and mediates its response upon stimulation of insulin-like growth factorbinding protein 3 (IGFBP-3) (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…However, LRP-1 also regulates signaling cascades by binding growth factors such as platelet-derived growth factor (49), CTGF (50), and TGF-␤ (51, 52). Interestingly, several of these molecules also bind decorin (53)(54)(55). Type V TGF-␤ receptor was found to be identical to LRP-1 (56) and mediates its response upon stimulation of insulin-like growth factorbinding protein 3 (IGFBP-3) (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…NPN Inhibits TGF-␤/Smad Signaling-It has been reported that several SLRP members, including DCN, interact with a number of growth factors such as TGF-␤ (22, 23), platelet-derived growth factor (30), and insulin-like growth factor-1 (31), and modulate their activities. Because we have identified the NPN gene based on the structural similarity to DCN, we investigated the possible regulatory function of NPN in TGF-␤ signaling.…”
Section: Npn Belongs To a New Class Of The Slrp Family-basedmentioning
confidence: 99%
“…Importantly, many of these cell functions are controlled by growth factors and cytokines (TGFβ, TNFα and PDGF) that are stored in the ECM and presented to cells as they interact with and remodel the matrix. The types of control mechanisms employed include secretion of growth factors in latent form, storage in the ECM by use of specific binding proteins to prevent receptor binding, activation of latent or bound forms via proteolytic processing [1719], and modulation of receptor activity [20,21]. Indeed, our previously published studies have shown that ECM proteins regulate MSC behavior by modulating both endogenous (stem cell-derived) and exogenous (externally added or serum-derived) growth factor stores [10,12,14,22].…”
Section: Introductionmentioning
confidence: 99%